MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA DINI MELALUI BERCERITA PANGGUNG BONEKA - Ilzam Dhaifi; Wardatul Jannah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2021)
A very important factor for children in expressing their emotions is through language. Language for children can be obtained through their experiences in daily life. One method that can be an alternative in developing language for early childhood is using the puppet stage storytelling method. Through listening activities, children can absorb the information contained in the story. The formulation of the problem in this study is (1) How is the implementation of improving early childhood language skills through storytelling on a puppet stage in group B children?. (2) How are the results of improving early childhood language skills through puppet stage storytelling in group B children. This type of research is Classroom Action Research (CAR) with problem solving carried out in cycles. Each cycle consists of planning, action, observation and reflection with the aim of improving the quality of classroom learning. While the results of this study include; (1) The process of implementing the storytelling on the puppet stage begins with asking the children to line up in a circle to tell the story on the puppet stage. The teacher calls the children one by one to come to the stage and the children start telling stories in turn according to the teacher's directions. (2) the results of the study showed an increase in aspects of children's language skills through puppet stage storytelling, namely pre-cycle, the percentage value reached 30%. With an average value of 3.9, after the first cycle of action, the percentage value reached 50%. With an average value of 5.2. The second cycle of action, the percentage value reached 80%, with an average value of 6.7%.